Viral Nervous Necrosis due to Betanodavirus: A Case Study in Pot‐Bellied Seahorses ( Hippocampus abdominals ) - Stephen M. Pefanis; Graeme Knowles; Peter G. Mohr; Kate Swift; Jemma Bergfeld; Teresa K. Wilson; Marianne Douglas; Rachelle Hawkins; John Hoad; Adam Costin; Jacqueline Morris; David Cummins; et al. (Journal of Fish Diseases, 2025)
Betanodaviruses, members of the Nodaviridae family, are the causative agents of viral nervous necrosis in fish, resulting in great economic losses worldwide. This is the first case study describing the detection and confirmation of viral nervous necrosis in pot‐bellied seahorses ( Hippocampus abdominalis ) in Australia. Clinical signs of this infection in the seahorses included whirling, floating and cessation of feeding. Histopathological findings included prominent vacuolation in the grey matter of the brain and in the retina of the eye. Betanodavirus infection was initially detected by betanodavirus reverse transcriptase quantitative PCR and nested PCR. Sequencing confirmed the red‐spotted grouper nervous necrosis virus (RGNNV) genotype of betanodavirus. The RGNNV genotype of betanodavirus has previously been detected in Australia in fish, including barramundi ( Lates calcarifer ) and striped trumpeter ( Latris lineata ). Immunohistochemistry using antibodies directed against the capsid protein of betanodavirus demonstrated intralesional virus antigen. Betanodavirus targeted the brain, spinal cord and retina, causing intracytoplasmic vacuolation of neuronal processes and neuronal necrosis.

Sustainable mining in tropical, biodiverse landscapes: Environmental challenges and opportunities in the archipelagic Philippines - Justine Perry T. Domingo; Gawen R.T. Jenkin; Laura Quick; Richard D. Williams; Karen A. Hudson-Edwards; Cecilia Tortajada; Patrick Byrne; Tom J. Coulthard; Jenielyn T. Padrones; Rich Crane; Cris Reven L. Gibaga; Grigorios Vasilopoulos; et al. (Journal of Cleaner Production, 2024)